(untitled) - Loftas, Tony (Chicago, 1970)
The brief mentuion of national investment in marine resources leads to the main theme of the book, which is an attempt to show just what the oceans hold in store for those who turn to them.
Keywords: Tài nguyên biển,Marine resources